A legal history of consent and intervention in civil wars in Latin America. (2nd January 2020) - Gurmendi Dunkelberg, Alonso
ABSTRACT: Recently, international law has seen renewed interest in the topic of intervention by invitation. Despite this, Latin American views have remained absent from the conversation. This article rediscovers the history of intervention by invitation in Latin American civil wars, focusing specifically on the issue of consent and the role it played in two key events of the region's early legal history: the War of the Confederation and the Gorostiza Pamphlet affair. It finds that, in those cases, the right of a state to consent to intervention in a civil war was not questioned, but rather, expressly affirmed. In this vein, and despite a lack of more recent practice, while Latin America's experience with European interventionism indicates a strong tradition of non-interventionism, its experience with civil war seems to point towards a preference for government consent over strict-abstentionism as a guiding principle.